Agreement between Polar and SRM mobile ergometer systems during laboratory-based high-intensity, intermittent cycling activity - Hurst, H. T.; Atkins, S. (Journal of Sports Sciences, 2006)
The purpose of this study was to assess the agreement between two mobile cycle ergometer systems for recording high-intensity, intermittent power output. Twelve trained male cyclists (age 31.4 ± 9.8 years) performed a single 3 min intermittent cycle test consisting of 12 all-out efforts, separated by periods of passive recovery ranging from 5 to 15 s. Power output was recorded using a Polar S710 heart rate monitor and power sensor kit and an SRM Powercrank system for each test. The SRM used torque and angular velocity to calculate power, while the S710 used chain speed and vibration to calculate power. Significant differences (P < 0.05) in power were found at 8 of the 12 efforts. A significant difference (P = 0.001) was also found when power was averaged over all 12 intervals. Mean power was 556 ± 102 W and 446 ± 61 W for the SRM and S710 respectively. The S710 underestimated power by an average of 23% with random errors of */÷ 24% when compared with the SRM. Random errors ranged from 36% to 141% with a median of 51%. The results indicate there was little agreement between the two systems and that the Polar S710 did not provide a valid measure of power during intermittent cycling activity when compared with the SRM. Power recorded by the S710 system was influenced greatly by chain vibration and sampling rates.